L’oppidum du Marduel (Saint-Bonnet-du-Gard) du Bronze final IIIb à l’époque romaine : synthèse des recherches sur un habitat occupé dans la longue durée - Denis Lebeaupin (Gallia)
The protohistoric settlement of Marduel in Saint-Bonnet-du-Gard (Gard) is located between Nimes and Avignon, on the banks of the River Gardon. Excavations were conducted between 1975 and 1990 under the direction of Michel Py, mainly on the upper settlement, whereas the lower part of the site was only superficially identified. Those works were published in six articles in Documents d’Archéologie Méridionale. This contribution is a synthesis of the research carried out at the site, and also takes into consideration the discoveries made in southern Gaul during the last decades.The oppidum of Marduel directly dominates a ford on the Gardon which was a compulsory crossing-point for several important routes, including the one linking Languedoc to the regions of the north of France by the right bank of the Rhône.The upper settlement was occupied during the final Bronze Age IIIB, in the first half of the 6th c. BC, from the end of the 6th c. BC to the change of era, and briefly in the first half of the 5th c. AD. The chronology of settlement in the plain, or the piedmont, is less well known, but it seems as though the zone was more or less continuously settled, or at least visited, from the final Bronze Age IIIB to the end of the 5th c. BC, unoccupied from the 4th c. to the 2nd c. BC, then settled again during the Roman period.The upper village was surrounded by a monumental stone fortification at the end of the 6th c. BC, encircling an area of about 5 ha. The rampart was mostly restructured in the second quarter of the 2nd c. BC.The excavation identified several domestic units with one or two rooms and tracked their evolution over 500 years, bringing to light the stability of the overall organization of the settlement and the permanence of architectural techniques from the middle of the 5th c. to the middle of the 1st c. BC.The diachronic study of the finds enables us to understand the economy of the community and in particular to follow the evolution of trade with the Mediterranean world. These exchanges appear to increase sharply from the beginning of the 6th c. to the middle of the 5th c. BC, then regress and remain at a low level until the 2nd c. BC. This decline does not seem to result from a considerable decrease in farming production, but can instead be explained by the insecurity that appears to set in during the second Iron Age, and perhaps by a breakdown in the terms of trade between native communities and their trade partners, Mediterranean traders and trading-post intermediaries.